The mediating power of sport : global challenges and sport culture in China - Tian, Enqing; Wise, Nicholas (Emerald Publishing Limited, 2024)
Given China's investment in sport, success in international competitions and recent hosting of high-profile events, there is no doubt the country is a rising power in the realm of global sports. Encouraging readers in other international settings to consider this topic from their own cultural contexts, this collection addresses the question of why China has so tightly embraced modern sport. How does this interact with China's mediated ability to play and compete with the west? The first English collation of works from both established and emerging sociological scholars on sport culture in China, this collection analyses how sport is seen as a channel of observing global, political and economic challenges. Bringing a foundational Chinese context to each chapter, contributors analyse topics including traditional sports, nationalism, football fandoms, commercialisation and esports. Offering critical insights into 'glocalized' sporting cultures and political hegemony, authors dig deep into common sociological theories to address issues around mediating power and China's sport culture. Examining the relationship between sport and social transformation, contributors also reflect on how we might research the sociology of sport in China going forward. Exploring how sporting cultures, practices and attitudes differ across cultural settings, The Mediating Power of Sport demonstrates how China has created new forms of influence through sport and considers what this might mean for how we think about soft power, international prowess and the deeper role sport can play on the world stage.
Includes index.
Keywords: Sports -- Sociological aspects.; Sports -- China.; Sports & Recreation -- Cultural & Social Aspects.; Sociology: sport and leisure.; elektronické knihy; electronic books